The Role of Customer Satisfaction Mediates The in-Fluence of Store Atmosphere and Service Quality on Customer Loyalty - Wijana, I Made Michael; Bayu Rahanatha , Gede (Journal Of Social Science (JoSS), 2025)
The purpose of this study is to explain the role of customer satisfaction mediates the influence of store atmosphere and service quality on customer loyalty (a study on Warung Kopi Jenar Kaliasem customers). The theory used is the Stimulus-Organism-Response (SOR) theory. This research employed a non-random sampling method. The population in this study consists of people in Denpasar City with a minimum education level of high school or equivalent who have visited and purchased products at Warung Kopi Jenar at least twice within six months. The sample selection method used was judgment sampling, with a total of 120 respondents. Data collection was carried out by distributing questionnaires. The data analysis technique used in this study was PLS-based SEM. The results show that store atmosphere and service quality have a positive and significant effect on both customer satisfaction and customer loyalty. Customer satisfaction also has a positive and significant effect on customer loyalty. Mediation analysis indicates that store atmosphere and service quality affect customer loyalty through customer satisfaction. The theoretical implications of this study reveal that store atmosphere and service quality influence customer loyalty not only directly but also indirectly through customer satisfaction as a mediating factor. Practically, these findings provide strategic insights for the managers of Warung Kopi Jenar regarding the important role of customer satisfaction in mediating the influence of store atmosphere and service quality on customer loyalty.